Chronic rhinosinusitis with nasal polyps is associated with impaired TMEM16A-mediated epithelial chloride secretion - Salomon, Johanna J.; Albrecht, Tobias; Gräber, Simon Y.; Scheuermann, Heike; Butz, Simone; Schatterny, Jolanthe; Mairbäurl, Heimo; Baumann, Ingo; Mall, Marcus A. (The journal of allergy and clinical immunology, 2021)
Background - Chronic rhinosinusitis with nasal polyps (CRSwNP) is one of the most common chronic disorders with limited therapeutic options. However, the pathogenesis of CRSwNP remains poorly understood. - Objective - We sought to determine the role of abnormalities in nasal epithelial ion transport in primary epithelial cultures and patients with CRSwNP. - Methods - We studied epithelial ion transport and transcript levels of the Cl− channels cystic fibrosis transmembrane conductance regulator and transmembrane protein 16A (TMEM16A) in human primary nasal epithelial cultures of patients with CRSwNP and healthy controls. Furthermore, we determined expression levels of proinflammatory cytokines that have been implicated in the regulation of epithelial ion channels (IL-1β, INF-γ, TNF-α, IL-13) and studied effects of the key TH2 signaling molecule IL-13 in CRSwNP and control nasal epithelial cultures. Finally, we measured in vivo nasal potential difference to compare epithelial ion transport in patients with CRSwNP and controls. - Results - Bioelectric studies demonstrated that Ca2+-activated Cl− secretion was reduced in CRSwNP versus control nasal epithelial cultures. Transcript levels of IL-13 and the Ca2+-activated Cl− channel TMEM16A were increased in CRSwNP cultures. Stimulation with IL-13 increased TMEM16A expression further and restored Ca2+-activated Cl− secretion in CRSwNP cultures. Nasal potential difference measurements demonstrated reduced Ca2+-activated Cl− transport in patients with CRSwNP versus controls. - Conclusions - This study demonstrates that TMEM16A-mediated Ca2+-activated Cl− secretion is reduced in primary nasal epithelial cultures and nasal epithelia of patients with CRSwNP. Our data suggest that the Ca2+-activated Cl− channel TMEM16A may be implicated in the pathogenesis and serve as a novel therapeutic target in patients with CRSwNP.
Gesehen am 04.08.2021